A phase 2 randomised study of veliparib plus FOLFIRI±bevacizumab versus placebo plus FOLFIRI±bevacizumab in metastatic colorectal cancer - Gorbunova, Vera; Hofheinz, Ralf-Dieter (British journal of cancer, 2019)
Metastatic colorectal cancer (mCRC) has low survival rates. We assessed if addition of veliparib, concurrent to FOLFIRI, improves survival in patients with previously untreated mCRC. This study compared veliparib (200 mg BID for 7 days of each 14-day cycle) to placebo, each with FOLFIRI. Bevacizumab was allowed in both arms. The primary endpoint was progression-free survival (PFS). Patients were randomised to receive veliparib (n = 65) or placebo (n = 65) in combination with FOLFIRI. Median PFS was 12 vs 11 months (veliparib vs placebo) [HR = 0.94 (95% CI: 0.60, 1.48)]. Median OS was 25 vs 27 months [HR = 1.26 (95% CI: 0.74, 2.16)]. Response rate was 57% vs 62%. Median DOR was 11 vs 9 months [HR = 0.73 (95% CI: 0.38, 1.40)]. AEs with significantly higher frequency (p < 0.05) in the veliparib group were anaemia (39% vs 19%, p = 0.019) and neutropenia (66% vs 37%, p = 0.001) for common AEs (≥20%); neutropenia (59% vs 22%, p < 0.001) for common Grade 3/4 AEs (≥5%); none in serious AEs. Haematopoietic cytopenias were more common with veliparib (79% vs 52%, p = 0.003). Fourteen percent of patients on veliparib and 15% on placebo discontinued treatment due to AEs. Veliparib added to FOLFIRI ± bevacizumab demonstrated similar efficacy as FOLFIRI ± bevacizumab in frontline mCRC patients. No unexpected safety concerns occurred.